Cross Institutional Synergy in Regional Livestock Control Implementation: Sinergi Lintas Lembaga dalam Implementasi Pengendalian Ternak Daerah - Ardiansah, Ardiansah; Djaafar, Lucyane; M. Wantu, Sastro (Universitas Muhammadiyah Sidoarjo, 2026)
Abstract General Background: Regional policy implementation frequently encounters structural and socio-cultural barriers, particularly in regulating public order within rural governance contexts. Specific Background: The implementation of Regional Regulation Number 3 of 2022 concerning livestock control in Moutong District, Parigi Moutong Regency, demonstrates persistent issues, including weak cross-agency coordination, low public legal awareness, inconsistent sanction enforcement, limited facilities, and reactive control patterns. Knowledge Gap: Although both top-down administrative mechanisms and bottom-up community initiatives have been introduced, their interaction has not been systematically conceptualized within an integrated cross-institutional synergy framework. Aims: This study aims to analyze the formation of cross-institutional synergy through the integration of top-down and bottom-up approaches in implementing livestock control policy and to identify determining factors shaping its implementation. Results: Using a descriptive qualitative method with interviews, observations, and documentation, the findings reveal that implementation remains suboptimal due to incidental coordination, dominance of hierarchical directives, uneven sanction application, limited resources, and fragile public trust. However, emerging collaborative practices—such as village livestock task forces, digital reporting mechanisms, vulnerability-based standard operating procedures, and community monitoring—indicate the potential of structured synergy. Novelty: This study constructs a dual-model synergy scheme that integrates hierarchical policy instruments with community-based participation to bridge the gap between normative regulation and social practice. Implications: The findings highlight the necessity of institutionalized coordination, consistent law enforcement, strengthened community engagement, and adaptive governance mechanisms to achieve sustainable livestock control within decentralized regional administration. Highlights• Field coordination remains incidental with uneven sanction practices and limited operational facilities.• Public trust and local creativity shape compliance and collaborative governance capacity.• Integrated hierarchical directives and community-driven initiatives form an adaptive governance scheme. KeywordsCross Institutional Synergy; Policy Implementation; Livestock Control; Regional Regulation; Collaborative Governance